Analysis on Optimal Mode of Operation of Small and Medium Pumped Storage Power Station. Issue 1 (March 2021) - Zhang, Yi; Zhang, Feng; Li, Youchun; Mo, Jianguo; Tang, Lv
Abstract: With the rapid development of new energy and peak-shaving of power grid, pumped storage power station has been paid more and more attention as an economical and reliable means of peak-shaving. Pumped storage power station can play the role of peak-shaving frequency modulation, accident reserve, black start power supply and so on. It is an effective means to ensure the safe operation of power grid, optimize the economic operation of thermal power units and promote the absorption of new energy. This paper first briefly introduces the operation mode of pumped storage power station, and analyzes the operation benefit of pumped storage power station from the actual operation demand of power grid. Further, the main operation mode of pumped storage power station is analyzed, and the operation mode suitable for small and medium pumped storage power station is put forward.